2003
DOI: 10.1002/path.1473
|View full text |Cite
|
Sign up to set email alerts
|

Are tumours angiogenesis‐dependent?

Abstract: The final proof of principle that cancer patients can be effectively treated with angiogenesis inhibitors is eagerly awaited. Various preclinical in vivo experiments have proven that most tumours need new vessel formation in order to grow and to form metastases. First of all, tumours do not grow in avascular corneas until new blood vessels reach the implant. Secondly, the introduction of only one angiogenic gene can cause a switch from tumour dormancy to progressive tumour growth. Thirdly, tumour growth can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 79 publications
0
67
0
7
Order By: Relevance
“…These unusual features provide some molecular and structural basis for selective inhibition or even destruction of tumor vessels by angiogenesis inhibitors (Cao, 2004). By attacking the vascular compartment with specific angiogenesis inhibitors, tumor growth can be inhibited and sometimes tumor regression can be obtained (Verheul et al, 2004). However, several clinical trials have shown mild results, and resistance to the treatment has also been observed.…”
Section: Angiogenesis Inhibition and Vascular Targetingmentioning
confidence: 99%
“…These unusual features provide some molecular and structural basis for selective inhibition or even destruction of tumor vessels by angiogenesis inhibitors (Cao, 2004). By attacking the vascular compartment with specific angiogenesis inhibitors, tumor growth can be inhibited and sometimes tumor regression can be obtained (Verheul et al, 2004). However, several clinical trials have shown mild results, and resistance to the treatment has also been observed.…”
Section: Angiogenesis Inhibition and Vascular Targetingmentioning
confidence: 99%
“…Physiologic imaging such as perfusion MR imaging has been used recently to evaluate angiogenesis, which is important for both the growth and metastasis of malignant tumors. 2 The 2 most common MR perfusion techniques used in clinical practice are dynamic susceptibility-weighted contrast-enhanced imaging and DCE imaging. 3 Following an intravenous injection of a Gd-based contrast agent, dynamic susceptibilityweighted contrast-enhanced imaging measures the change in R 2 * during the first pass of the bolus, while DCE imaging measures the changes in R 1 during both the first pass and washout phases.…”
mentioning
confidence: 99%
“…Angiogenesis is the sprouting of blood vessels from preexisting ones where endothelial buds grow out towards the tumor margins [32][33][34][35][36]. Reciprocal paracrine interactions between astrocytes, endothelial cells and ependymal cells have been demonstrated in recent studies.…”
Section: Discussionmentioning
confidence: 99%